Rediscovery of the hadal species Amblyops magnus Birstein & Tchindonova, 1958 (Crustacea: Mysida: Mysidae): first record from the Mariana Trench - Kou, Qi; Li, Xinzheng; He, Lisheng; Wang, Yong (Zootaxa, 2018)
The blind deep-sea mysid Amblyops magnus Birstein & Tchindonova, 1958 is recorded for the first time from the Mariana Trench based on an adult female specimen collected near the Challenger Deep at a depth of 6555 m. The specimen was described, illustrated and compared with the type description as well as with the materials previously collected from the Japan Trench. The mitochondrial COI barcode was also obtained from the specimen and submitted to GenBank. This is the third discovery of this rare species and significantly extends its geographic distribution range to the low latitude hadal zone.